2008
DOI: 10.1080/09297040802577311
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning in Children and Adolescents with Major Depressive Disorder

Abstract: The present investigation examined neurocognitive functioning, focusing on executive functioning (EF), in 39 children and adolescents with Major Depressive Disorder (MDD) and 24 healthy control subjects all ages 8 to 17 years. The Wechsler Intelligence Scale for Children-Third Edition along with several measures of executive functioning including the Wisconsin Card Sorting Task, Trail Making Test, Controlled Oral Word Association Test, and the Stroop Color Word Test were administered. The neurocognitive profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 30 publications
8
49
1
1
Order By: Relevance
“…For instance, the speed at which women with and without a SAH respond (i.e., how long they stay in the scene) is a primary difference reported in the literature. However, no studies to-date have controlled for depressive symptoms, which are common in sexual assault survivors [22,23] and are related to psychomotor slowing [24] and slower processing speed [25]. Similarly, a recent study utilized a written vignette and replicated the finding that women with a SAH left later in the scene [26].…”
Section: Introductionmentioning
confidence: 70%
“…For instance, the speed at which women with and without a SAH respond (i.e., how long they stay in the scene) is a primary difference reported in the literature. However, no studies to-date have controlled for depressive symptoms, which are common in sexual assault survivors [22,23] and are related to psychomotor slowing [24] and slower processing speed [25]. Similarly, a recent study utilized a written vignette and replicated the finding that women with a SAH left later in the scene [26].…”
Section: Introductionmentioning
confidence: 70%
“…Klimkeit et al [46] noted this deficit only in the dysthymic/depressive disorder not otherwise specified group but not the major depressed group. Investigating only the phonemic component, two other studies did not observe group differences [23,39].…”
Section: Verbal Fluencymentioning
confidence: 96%
“…This study had a high rate of comorbidity with anxiety, which means that impaired performance on the TMT B may have been due to the presence of anxiety rather than depression. Favre et al [23] found no significant group differences but noted greater variance in the performance of a larger group of children and adolescents with MDD. They also found no group difference on the Wisconsin Card Sorting Test (WCST).…”
Section: Set Shiftingmentioning
confidence: 96%
See 1 more Smart Citation
“…We developed a demography measure assessing education, employment, change to living arrangements and friendship groups over the preceding year to account for any effects of environment on functional change. Participants were asked to report current mental illness and mood state because this may have affected task performance, although current findings are equivocal in relation to mood state and cognitive function (Uekermann et al, 2008;Favre et al, 2009). …”
Section: Methodsmentioning
confidence: 99%